Pengaruh Kualitas Produk dan Citra Merek terhadap Kepuasan Konsumen Skincare Ms Glow di Singaraja - Roma Natalia Margaretha; Made Putri Ariasih (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the influence of product quality and brand image variables on consumer satisfaction. The focus of this study is the people of Singaraja City who use MS Glow skincare products. The research method used is quantitative with a causal approach, aiming to determine the relationship between the variables studied. The population in this study includes consumers who have purchased and used MS Glow skincare products in the Singaraja area. The sampling technique used is non-probability sampling with a total of 140 respondents. The independent variables in this study include product quality (X1) and brand image (X2), while the dependent variable is consumer satisfaction (Y). Data were collected by distributing questionnaires to respondents who have met the criteria, and then analyzed using the SPSS version 30.0 program. The data analysis technique used is multiple linear regression, to determine the influence of each independent variable on the dependent variable both partially and simultaneously. The results of the study indicate that: (1) product quality has a positive and significant influence on consumer satisfaction; (2) brand image also has a positive and significant influence on consumer satisfaction; and (3) simultaneously, product quality and brand image significantly influence consumer satisfaction among MS Glow skincare users in Singaraja. These findings provide important implications for companies in improving product quality and building a positive brand image to maintain consumer satisfaction.